Peran “Orang Lain” dalam Pembentukan Self Confidence dalam Menghadapi Body Shaming (Analisis Isi Film Imperfect) - Oktaviani, Reka Ayu; Jumriani; Subekti Masri (Communication and Islamic Broadcasting Studies IAIN Parepare, 2024)
This thesis discusses the problem of body shaming in the film Imperfect. The research objectives are: To find out the effect of body shaming on Rara's self-confidence, to find out the forms of verbal and non-verbal communication of other people in forming Rara's self-confidence, and to find out the role of other people in forming self-confidence in dealing with Rara's body shaming in the film Imperfect . This research uses qualitative research (Document Study), while the data source is the film Imperfect; Career, Love and Scales watched live via Facebook Social Media. In this research, the researcher acts as a research instrument using tools, namely the Imperfect video film, by taking pieces of images, scenes and dialogue, data is obtained through observation and documentation. Next, the research data was analyzed using Philipp Mayring's content analysis. The results of this study show that: 1. The influence of body shaming on Rara's self-confidence is divided into two, namely negative consisting of feeling insecure and not confident, liking to be alone, far from success, doing extreme things and changing attitudes, positive consisting of diligently exercising, after There was a change, Rara looked more confident, and was accepted as manager of her company. 2. Forms of verbal and nonverbal communication from other people in forming Rara's self-confidence, verbal is characterized by advice, suggestions, ideas while non-verbal communication is characterized by hugs, touches, body movements and vocals 3. The role of other people in forming Rara's self-confidence in the face of body shaming. divided into emotional support, information support, instrumental support and appreciation support